Analisis Perubahan Penggunaan Lahan dan Daya Dukung Lahan Pertanian Sawah di Kecamatan X Koto Tahun 2005-2023 - Ramadani, Nadila; Suasti, Yurni (Lembaga Yasin AlSys, 2025)
The objectives of this study are: (1) To analyze the extent of changes in the use of rice field agricultural land in X Koto District in the period of 2005-2014 and the period of 2014-2023, (2) To analyze the carrying capacity of rice field agricultural land in X Koto District for the period of 2005-2014 and the period of 2014-2023. This type of research uses a quantitative descriptive method with secondary analysis. The data used are secondary data in the form of Landsat 7 ETM Satellite Imagery in 2005, Landsat 8 OLI Imagery in 2014 and 2023, as well as data on the area of rice harvested land, the number of population, and the average rice production in X Koto District for the period of 2005-2014 and the period of 2014-2023. The data analysis technique uses Supervised Classification. The analysis of changes in rice field agricultural land in this study uses the overlay technique. The researcher found: (1) The area of rice field agricultural land in 2005 was 1973.40 ha, then in 2014 it decreased to 1513.15 ha with a reduction rate of 23.32%. In 2023, the area of paddy field agricultural land will decrease again to 1265.76 ha with a reduction rate of 16.34%. (2) In the period of 2005-2014, the carrying capacity of rice field agricultural land in X Koto District was 1.74 and the period of 2014-2023 was 1.89. X Koto District is an area with food self-sufficiency, where the area is able to meet the basic needs of the community, but has not been able to provide a decent life for its residents.